Age-of-infection and the final size relation - Fred Brauer (Mathematical Biosciences and Engineering)
We establish the final size equation for a general age-of-infection epidemic model in a new simpler form if there are no disease deaths(total population size remains constant). If there are disease deaths, the final size relation is an inequality but we obtain an estimate for the final epidemic size.